International cooperation for countering terrorism within the UN: theoretical-empirical aspects - Cristina EJOVA (CES Working Papers, 2023)
This paper explores the policies of the United Nations and specialized institutions concerning the coordination of international community efforts to combat terrorist threats. Terrorism remains a significant threat to international security, despite the war in Ukraine taking priority in terms of insecurity. In this regard, international cooperation aimed at countering terrorism remains relevant, and the actions taken between 2015 and 2018 must be expanded and intensified. Such cooperation requires the participation of a broad spectrum of actors in international relations, including states, governmental international organizations, and civil society. Terrorism continues to be a global problem, and multilateral cooperation is both timely and necessary to counter it. Terrorist movements have not taken a break, despite their lack of large-scale actions, as they continue to express themselves through the activities of crisis cells or lone wolves. Consequently, prophylaxis methods must be supplemented, considering the new forms of terrorism expression. The United Nations organization continues to prove itself as the institution authorized to develop the legal framework and coordinate international efforts to counter this scourge.